2019
DOI: 10.1038/s41556-018-0223-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrin trafficking in cells and tissues

Abstract: Cell adhesion to the extracellular matrix (ECM) is fundamental to metazoan multicellularity and is accomplished primarily through the integrin family of cell-surface receptors. Integrins are internalised and enter the endo/exocytic pathway before being recycled back to the plasma membrane. The trafficking of this extensive protein family is regulated in multiple context-dependent ways to modulate integrin function in the cell. Here we discuss recent advances in understanding the mechanisms and cellular roles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
310
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(318 citation statements)
references
References 148 publications
(184 reference statements)
6
310
0
2
Order By: Relevance
“…Several studies have shown that nociceptive sensory terminals share a close relationship with specific extracellular structures, most notably epidermal cells and extracellular matrix (ECM), yet whether paclitaxel impact this relationship is unknown. Integrins are a key mediator of the interaction between cells and the ECM, and impact neuronal maintenance in both vertebrate and invertebrate systems (Han et al, 2012;Kim et al, 2012;Moreno-Layseca et al, 2019;Nieuwenhuis et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that nociceptive sensory terminals share a close relationship with specific extracellular structures, most notably epidermal cells and extracellular matrix (ECM), yet whether paclitaxel impact this relationship is unknown. Integrins are a key mediator of the interaction between cells and the ECM, and impact neuronal maintenance in both vertebrate and invertebrate systems (Han et al, 2012;Kim et al, 2012;Moreno-Layseca et al, 2019;Nieuwenhuis et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Conceivably, these changes could include reduction in de novo integrin synthesis, reduced integrin recycling, and/or increased integrin degradation. Prior studies in other systems indicate that integrin levels are maintained by continuous recycling via tight regulation of the endosomal pathway rather than degradation and de novo synthesis (Moreno-Layseca et al, 2019). We therefore investigated potential changes caused by paclitaxel in endosomal and lysosomal pathways in nociceptive neurons in Drosophila.…”
Section: Paclitaxel Disrupts Endosomal-lysosomal Pathways and Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…AP-2 is well known for its role in facilitating clathrin-mediated endocytosis of integrins (De Franceschi et al, 2016;Moreno-Layseca et al, 2019). Thus we wondered, if AP-1B would colocalize with AP-2.…”
Section: Ap-1b Does Not Colocalize With Ap-2mentioning
confidence: 96%